2014
DOI: 10.1186/scrt500
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic-turmerone induces neural stem cell proliferation in vitro and in vivo

Abstract: IntroductionAromatic (ar-) turmerone is a major bioactive compound of the herb Curcuma longa. It has been suggested that ar-turmerone inhibits microglia activation, a property that may be useful in treating neurodegenerative disease. Furthermore, the effects of ar-turmerone on neural stem cells (NSCs) remain to be investigated.MethodsWe exposed primary fetal rat NSCs to various concentrations of ar-turmerone. Thereafter, cell proliferation and differentiation potential were assessed. In vivo, naïve rats were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 35 publications
1
45
0
Order By: Relevance
“…Besides transplanted cells, endogenous NSC can be mobilized from their neurogenic niches, namely the subventricular zone (SVZ) and the subgranular zone (SGZ) of the hippocampus. However, the intrinsic potential of endogenous NSC is insufficient and external stimuli are necessary to fully exploit their therapeutic potential (Arvidsson et al 2002;Lee et al 2012;Rueger et al 2012;Hucklenbroich et al 2014;Lindvall and Kokaia 2015;Rabenstein et al 2015;Braun et al 2016). The small NCAM-derived peptide FGL crosses the blood-brainbarrier and constitutes an attractive candidate molecule for enhancing the therapeutic potential of endogenous NSC and may thus open a new therapeutic vista.…”
Section: Discussionmentioning
confidence: 98%
“…Besides transplanted cells, endogenous NSC can be mobilized from their neurogenic niches, namely the subventricular zone (SVZ) and the subgranular zone (SGZ) of the hippocampus. However, the intrinsic potential of endogenous NSC is insufficient and external stimuli are necessary to fully exploit their therapeutic potential (Arvidsson et al 2002;Lee et al 2012;Rueger et al 2012;Hucklenbroich et al 2014;Lindvall and Kokaia 2015;Rabenstein et al 2015;Braun et al 2016). The small NCAM-derived peptide FGL crosses the blood-brainbarrier and constitutes an attractive candidate molecule for enhancing the therapeutic potential of endogenous NSC and may thus open a new therapeutic vista.…”
Section: Discussionmentioning
confidence: 98%
“…Among turmerons, arturmerone is a major bioactive compound of C. longa. It has been suggested that ar-turmerone inhibits microglia activation, a property that may be useful in treating neurodegenerative disease (Hucklenbroich et al 2014).…”
Section: Composition Of Essential Oilmentioning
confidence: 99%
“…Endogenous neurogenesis activating after infarction is insufficient to repair the damaged area of brain by itself [7] . Thus, promoting the proliferation and migration of endogenous/transplanted NSCs is a promising therapeutic target for ischemic infarction [8][9][10] . HIF-1α is constitutively expressed but is degraded rapidly by 26s proteasomes in normoxia in most cells.…”
Section: Research Articlementioning
confidence: 99%